A New Technique in Tamai Zone 1 Reconstruction: Reverse Dorsal Terminal Vein Flap (Hat Flap) - Ince, Bilsev; Cem Yildirim, Mehmet Emin; Dadaci, Mehmet; Yarar, Serhat (Journal of Hand and Microsurgery, 2019)
Introduction The aim of this study was to determine usability of the reverse dorsal terminal vein flap (hat flap) in the reconstruction of Tamai zone 1 defects.Materials and Methods A total of 31 patients with fingertip amputation in Tamai zone 1 defect in the finger operated upon between 2014 and 2016 were included in this study. Flaps were designed from the proximal end of the nail bed to the middle phalanx according to the defect size. After passing through the skin, the proximal parts of the dorsal vein and branches were knotted. The flap was harvested by preserving the paratenon and dorsal digital terminal vein. Then, the flap was rotated and the defect was closed.Results A total of 32 patients were included in this study. The average size of the defects was 2 × 2.2 cm. Loss of epidermis in five patients and partial flap loss in two patients were observed (7/32, 21.8%), but total flap loss was not observed in any patient.Conclusion The reverse flow terminal dorsal vein-based pedicle flaps can be used as a viable surgical technique in the reconstruction of Tamai zone 1 amputations.Level of Evidence This is a Level IV study.
Keywords: fingertip amputation; venous flaps; reverse digital flap; fingertip reconstruction